2013
DOI: 10.1016/j.bpj.2013.01.054
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Polar Residues in the DAP12 homodimer: TOXCAT and Molecular Dynamics Simulation Studies

Abstract: Dimerization of the transmembrane (TM) adaptor protein DAP12 plays a key role in mediating activation signals through TM-TM association with cell-surface receptors. Herein, we apply the TOXCAT assay and molecular dynamics simulation to analyze dynamics and dimerization of the TM helix of DAP12 in the membrane bilayer. In the TOXCAT assay, we performed site-specific mutagenesis of potential dimerization motifs in the DAP12 TM domain. Instead of the common GxxxG dimerization motif, mutating either of the polar r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 53 publications
1
25
0
Order By: Relevance
“…The homodimeric DAP12 interface was first directly observed in NMR studies of DAP12 TM peptides reconstituted in detergent micelles (Call et al, 2010), revealing how its composite surface accommodates a single receptor TM helix containing a central lysine residue aligned with aspartic acid/threonine motifs that form the receptor-assembly site on DAP12. This has become an important model system for studies of immunoreceptor assembly (Cheng and Im, 2012; Sharma and Juffer, 2013; Wei et al, 2014; Wei et al, 2013) because similar arrangements of polar residues are believed to form the core TM structures of more complex receptor systems such as the hexameric NKG2D-DAP10 receptor implicated in anti-tumor immune responses (Garrity et al, 2005; Raulet et al, 2013) and the octameric T cell antigen receptor (TCR) that occupies a central position in adaptive immunity (Call et al, 2002). Importantly, no detailed structures of these intact complexes have been experimentally determined, and the mechanisms of signal transmission through the cell membrane remain poorly understood for the entire class of multi-subunit activating immune receptors.…”
Section: Introductionmentioning
confidence: 99%
“…The homodimeric DAP12 interface was first directly observed in NMR studies of DAP12 TM peptides reconstituted in detergent micelles (Call et al, 2010), revealing how its composite surface accommodates a single receptor TM helix containing a central lysine residue aligned with aspartic acid/threonine motifs that form the receptor-assembly site on DAP12. This has become an important model system for studies of immunoreceptor assembly (Cheng and Im, 2012; Sharma and Juffer, 2013; Wei et al, 2014; Wei et al, 2013) because similar arrangements of polar residues are believed to form the core TM structures of more complex receptor systems such as the hexameric NKG2D-DAP10 receptor implicated in anti-tumor immune responses (Garrity et al, 2005; Raulet et al, 2013) and the octameric T cell antigen receptor (TCR) that occupies a central position in adaptive immunity (Call et al, 2002). Importantly, no detailed structures of these intact complexes have been experimentally determined, and the mechanisms of signal transmission through the cell membrane remain poorly understood for the entire class of multi-subunit activating immune receptors.…”
Section: Introductionmentioning
confidence: 99%
“…Computer simulations of coarse‐grained molecular dynamics (CG MD), CG MD‐based potential of mean force (PMF) calculation and all‐atom simulation serve as complementary approaches to reproduce the results observed in TOXCAT experiments and provide more details of the PSGL‐1 assembly. The CG MD simulation is highly useful to investigate large systems, such as the conformational dynamics and the structural details of TM dimers and their interactions with lipid membranes . The PMF calculation method provides a view of the free energy landscape to predict and analyze the helix‐helix interactions of the TMD dimer in a lipid bilayer, and it has been confirmed that the free energies of dimerizaition in the CG model are similar to those from more detailed all‐atom simulations .…”
Section: Introductionmentioning
confidence: 78%
“…AT simulations of RH1 and RH2 were each performed for 50 ns with three independent samples as previous described (41)(42)(43). C␣ RMSD analysis showed that RH1 and RH2 models were both relatively stable because of the mild drift (Fig.…”
Section: A Packing Switch Pattern Of Cd36 Tm1 Homodimer In a Dppc Bilmentioning
confidence: 99%
“…Water molecules defined as the SPC model were added. The detailed simulation parameters were adopted as previous described (41,42). For each system, three replicas with different initial velocities were performed for 50 ns.…”
Section: At Simulationsmentioning
confidence: 99%
See 1 more Smart Citation